Review Of Basic Techniques In Club Volleyball, Pekanbaru City Transportation Office - Hermit Zalukhu; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is to see the basic technical skills of volleyball Pekanbaru City Transportation Department club. Based on the results of observations made at the Pekanbaru City Transportation Service club, several problems were found, including passing due to the ball being hit on the finger incorrectly, errors occurring in serving, not following the rules that have been explained so that the ball being served does not reach the opponent's court. or less than optimal, when smashing, the strength of the arm muscles and handling of the ball when smashing is less accurate, and the player's discipline must be improved in carrying out training more seriously and following all the rules. The tests used in this research used the under serve, under pass and smash tests in volleyball. The sample in this study was 12 people. From the results of tests carried out on volleyball athletes from the Pekanbaru City Transportation Service club, results were obtained in the